Pendidikan Paralegal Bagi Masyarakat Sebagai Wujud Pemenuhan Hak Asasi Manusia Berkelanjutan - Gunawan, Yordan; Hafiz, Mohammad Bima Aoron (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
Paralegals are parties that can provide advocacy or legal assistance to the people in a broad sense beside advocates, lecturers and other legal activists. The role of paralegal itself is not intended to replace the function of an advocate. Instead, it is aimed to be able to cooperate in the fulfillment of access to justice for the society, especially the people who are poor and other vulnerable groups. In Indonesia, paralegal position is a voluntary activity in conducting empowerment process in the society. The beginning of this article will invite and provide understanding to readers to understand the definition and comprehension of paralegals, types, and their important role for the fulfillment of access to justice which is one of the most basic parts of human rights. Beside preparing a law-conscious society, paralegals also provide human rights protection to people who are having problems with law, until the stage of investigation in the police office. The villagers trained will get certification and verified by the government. The society service uses educational methods or approaches that are oriented to problem solving process using the pattern of education elements conducted systematically, directed and planned with the active participation of individuals, groups and society as a whole to find ways to solve problems faced by the society by paying attention to the surrounding socio-economic and local cultural factors. This approach is considered to be able to move the society dynamically towards progress as expected. Meanwhile, being participative is an approach that emphasizes on the efforts to increase the participation of the society or individuals directly in various processes and implementation of programs. The results of the service program are demonstrated with the establishment of a paralegal society, increased awareness and knowledge of the society on their rights in the field of law